2004
DOI: 10.1111/j.1532-5415.2004.52156.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of MK‐0677, an Oral Growth Hormone Secretagogue, in Patients with Hip Fracture

Abstract: Although MK-0677 treatment increased serum IGF-I, it is uncertain whether clinically significant effects on physical function were achieved. Measuring function in clinical trials in hip-fracture patients is difficult because of the lack of validated outcome measures, high variability, and the lack of a baseline assessment. Present functional performance measures may not be sufficiently responsive for use as the primary endpoint of small intervention studies; alternatively, stimulation of GH may not result in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 38 publications
(45 reference statements)
0
45
1
2
Order By: Relevance
“…A small double-blind study reported a lean body-preserving effect of short-term GH treatment (Hedström et al 2004) (Table) and another double-blind short-term GH therapy study showed a faster return to prefracture living (van der Lely et al 2000) (Table). This was in contrast to a recent 6 month-study with oral GH secretagogue given to hip fracture patients who reported no functional improvement from this treatment (Bach et al 2004) (Table). Moreover, there have been reports of serious side effects of GH treatment in acute critically ill patients (Takala et al 1999), but not in hip fracture patients when therapy was started 3-4 days postoperatively (Yeo et al 2003, Hedström et al 2004.…”
Section: Recombinant Human Growth Hormone and Igf-icontrasting
confidence: 48%
“…A small double-blind study reported a lean body-preserving effect of short-term GH treatment (Hedström et al 2004) (Table) and another double-blind short-term GH therapy study showed a faster return to prefracture living (van der Lely et al 2000) (Table). This was in contrast to a recent 6 month-study with oral GH secretagogue given to hip fracture patients who reported no functional improvement from this treatment (Bach et al 2004) (Table). Moreover, there have been reports of serious side effects of GH treatment in acute critically ill patients (Takala et al 1999), but not in hip fracture patients when therapy was started 3-4 days postoperatively (Yeo et al 2003, Hedström et al 2004.…”
Section: Recombinant Human Growth Hormone and Igf-icontrasting
confidence: 48%
“…Growth hormone therapy increases IGF-I levels, promotes anabolism and increases muscle strength in healthy elderly individuals, as well as in selected patient groups [48][49][50]. Therefore, ghrelin and GHS may also have therapeutic potential to assist in the recovery of frail patients who require nutritional support and conventional rehabilitation [51]. Indeed, we are currently evaluating whether repeated ghrelin administration during the perioperative period would promote functional recovery in elderly patients undergoing elective total hip replacement.…”
Section: Gh Deficiency-related Disordersmentioning
confidence: 99%
“…Chronic treatment with intranasal hexarelin [65], subcutaneous GHRP-2 [66] or oral GHRP-2 [67] increased growth velocity in growth hormone deficient children. The non-peptidic GHS MK-0677 was administered to women with osteoporosis [68] or to elderly patients with hip fractures [69] without clinical benefit. Ghrelin treatment of patients with cachexia shows some promise, potentially through ghrelin's ability to stimulate GH and appetitestimulating effect, which is discussed below [70][71][72][73].…”
mentioning
confidence: 99%